TATA KELOLA, KINERJA RENTABILITAS, DAN RISIKO PEMBIAYAAN PERBANKAN SYARIAH - Cahaya Ekaputri (Journal of Business & Banking, 2014)
This research aims to reveal how Good Corporate Governance (GCG) practices of Islamic banks in Indonesia are. It also examines the ability of Good Corporate Governance practices in increasing profitability performance and in decreasing financing risk. A purposive sampling as a sampling technique was used with sample consisting of 10 Islamic banks for the research period of 2010 through 2012. Secondary data were also used in which they were obtained from the financial statement, Good Corporate Governance reports and annual reports of Islamic Banks. It used composite score of Good Corporate Governance based on Peraturan Bank Indonesia 11/33/PBI/2009. The data were analyzed using descriptive analysis and multiple regressions analysis. It shows that Good Corporate Governance of Islamic banks in Indonesia have obeyed the regulation from Bank of Indonesia. Even so, sometimes some the banks have not been assessed in accordance with reality. Thus, sometimes there is no match between the self assessment score with practices. It also shows that Good CorporateGovernance practices of Islamic banks in Indonesia are not able to improve profitabilityperformances but can reduce financing risk.